Pemanfaatan Isoflavon dalam Pucuk Daun Indigofera zollingerian sebagai Sumber Fitoestrogen untuk Meningkatkan Produksi dan Reproduksi Puyuh Petelur (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
This research aimed to study the effect of utilizing top leave meal of indigofera (TLMI) (Indigofera zollingeriana) in diet to production and reproduction of quail. A completely randomized design with four treatments and four replications (ten quails in each replications) was used in this experiment . The treatment diets were R0 = control diet (without TLMI ), R1 = diet containing 6% TLMI, R2= diet containing 12% TLMI, R3= diet containing 18% TLMI.  The results showed that the treatments did not affect the age of sex maturity, fertility, hatchability,follicle weights as well as number of follicles. Conclusion of this study is that usage 6% top leave meal of Indigofera zollingeriana resulted the best fertility and hatchability.